(untitled) (Texas Journal of Philology, Culture and History, 2023)
Expressing refusals, denials, and surprises are important sociodramas features of speech acts in many cultures. The way these speech acts are expressed can reveal cultural attitudes towards politeness, hierarchy, and social norms.